Traffic noise analysis in the main roads of the city of Sarajevo - Palić, Nermin (Crisis Management Days, 2024)
This research paper presents a comprehensive analysis of traffic noise levels along the main roads of the City of Sarajevo. Adopting a spatial, temporal, legal, and normative framework of the research, the study aims to establish the level and impact of traffic noise on the urban environment and the quality of life of residents. The methodology employed for traffic noise measurement involves a systematic approach, utilizing sound level meters placed strategically along key roadways to capture representative data. These measurements are conducted at various times of the day (day/night), to account for fluctuations in traffic. The analysis of the measured noise values reveals significant variations in noise levels across different type of roads and times of day. By comparing the observed noise levels with established legal and normative standards, the research assesses the extent of compliance with regulatory frameworks and identifies areas of concern where noise mitigation measures may be necessary. Through the analysis, hotspots of excessive noise pollution are identified, pinpointing specific locations where intervention strategies could be implemented to reduce noise exposure for nearby residents. In conclusion, this research underscores the importance of addressing traffic noise as a critical environmental and public health issue in urban areas like Sarajevo. The study provides valuable insights for policymakers and urban planners to develop effective noise management strategies and enhance the overall quality of urban living.